2024
DOI: 10.1186/s12944-024-02005-3
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-glucose index and obstructive sleep apnea: a systematic review and meta-analysis

Amir Hossein Behnoush,
Amirmohammad Khalaji,
Elina Ghondaghsaz
et al.

Abstract: Background Obstructive sleep apnea (OSA) has a bidirectional association with metabolic syndrome, and insulin resistance (IR). The triglyceride-glucose (TyG) index could be a simply calculated marker of IR in OSA. However, its clinical application appears still limited. Hence, this systematic review and meta-analysis aimed to respond to this question by analyzing all the existing studies showing an association between OSA and the TyG index. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Hence, although other indices demonstrate strong predictive abilities for OSA, the TyG index retains unique advantages. A recent meta-analysis aligns with this viewpoint, thus suggesting that the diagnostic accuracy of the TyG index is similar to that of other anthropometric indices [ 23 ].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Hence, although other indices demonstrate strong predictive abilities for OSA, the TyG index retains unique advantages. A recent meta-analysis aligns with this viewpoint, thus suggesting that the diagnostic accuracy of the TyG index is similar to that of other anthropometric indices [ 23 ].…”
Section: Discussionmentioning
confidence: 71%
“…A recent meta-analysis indicated that the TyG index serves as a readily measurable indicator of insulin resistance and is employed in the assessment of OSA for both diagnostic and prognostic purposes. Patients with OSA exhibit significantly greater TyG index levels than healthy controls [ 23 ]. The TyG index may be an independent risk factor for OSA [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of obesity in patients with OSA is also an important factor exacerbating the risk of GID. Obesity may exacerbate the symptoms of GID by increasing the intra-abdominal pressure and causing metabolic disturbances 27 . In addition, obesity may also affect the rate of gastric emptying and the balance of intestinal flora, which may further exacerbate gastrointestinal problems 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, daytime fatigue and reduced energy levels can decrease motivation for physical activity, further promoting weight gain [ 30 ]. Moreover, evidence suggests that OSA itself can change the lipid profile [ 31 ]; OSA itself exacerbates lipid abnormalities by increasing insulin resistance and inflammatory responses, creating a negative feedback loop [ 32 , 33 ]. The elevation in blood lipids puts pressure on the cardiovascular system, elevating the workload of the heart and blood vessels, which is unfavorable for patients with OSA, as they are already under the cardiovascular burden caused by intermittent hypoxia.…”
Section: Discussionmentioning
confidence: 99%